SPIRITUAL EDUCATIONAL; MODEL PEMBELAJARAN DALAM MELEJITKAN KECERDASAN RUHANI ANAK - Mistria Harmonis; Tupliati Tupliati (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
This study aims to examine the Spiritual Educational learning model to jump-start children's spiritual intelligence. The research approach used is descriptive qualitative with case study type. The research site is located in Sinar Harapan Kindergarten, Probolinggo City. Data collection techniques by means of interviews and in-depth observation. Meanwhile, data analysis techniques include data reduction, data display, and data verification. The results of the study indicate that the Spiritual Educational learning model applies several Islamic learning activities on a regular and structured basis to boost children's spiritual intelligence. The implication is that it takes a variety of activities and a fun approach to be able to jump-start children's spiritual intelligence.